Analysis of the Application of Accounting Based on PSAP Number 13 at the UPTD Pasar Prabumulih Health Center - Bayu Dharmaraga Alkahfi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
Pasar Prabumulih Health Center is a regional public service agency that is required to carry out accounting and prepare financial reports in accordance with Government Accounting Standards (PSAP) No. 13. The purpose of this study was to determine the application of accounting at the Pasar Prabumulih Health Center. Types and sources of data are primary data and secondary data collected through interviews and documentation techniques. In this research, the writer uses descriptive method. The results of this study indicate that the Pasar Prabumulih Community Health Center has not fully implemented Financial Reporting Standards (PSAP) No. 13, the basis for accounting records and cash management is in accordance with PSAP, but at the summary stage there was a mistake where PPK Puskesmas did not journalize used inventory expenses. Then in the operational report there are unrecorded expenses so that the expenses do not show their true value, the same goes for reports on changes in equity because there are unrecorded expenses there is a misstatement report. As for the notes on the PPK Puskesmas financial reports, they haven't made them yet, but for the realization reports, reports on excess budget balances, cash flow reports, they are in accordance with PSAP No. 13.